Problems and implications of new economic development models for agriculture, food, the environment and rural poverty - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
Bib. p. 131-135. Pub. tambien en esp.